Exoplanet Detection of the Kepler Space Telescope through the Transit Method - Yang, Helin (Transactions on Computer Science and Intelligent Systems Research, 2024)
With the exploitation of resources and environmental pollution, the Earth has suffered countless damages. As a result, there are more and more environmental problems such as the greenhouse effect and desertification. People only have one home, one Earth, so if the Earth becomes extinct, people will not exist anymore. Therefore, people need to repair and protect the planet. Humans have tried many ways to protect the Earth, but some damage is irreversible. Thus, to find another home and save mankind long after, scientists began to detect some potentially habitable exoplanets. In 2009, the National Aeronautics and Space Administration (NASA) launched the Kepler Space Telescope (KST) to detect exoplanets through the transit method. Surprisingly, it did find several exoplanets that are similar to Earth in some aspects. Unfortunately, with current technology, people can’t get there. This paper is going to introduce the KST, the transit method, and several potentially habitable exoplanets.